REASONS FOR TREATING GLOBAL ECONOMIC JUSTICE AS AN ESSENTIALLY CONTESTABLE CONCEPT - Lauer, Helen (European Scientific Journal, ESJ, 2013)
Contemporary theorists in the fields of international relations and global business ethics are generally gloomy about the extensive cultural diversity that underlies radically different value systems and political norms worldwide. This diversity is tacitly regarded as the bane of efforts to internationalise criminal law and principles of corporate social responsibility [CSR]. In this essay it is proposed, to the contrary, that cultural diversity is best regarded as a vehicle for discovering fundamental convictions about the meaning of global justice rather than the main obstacle to its realisation. An alternative to Hobbesian classic liberal derision of international law is proposed here by relying upon indigenous models of good governance and diplomacy that prevail in the midst of contemporary West Africa’s cultural diversity and economic distress. The possibility of global justice requires a conceptual change: from defining global justice as a fixed system of uniform procedures and implacable rules applied impartially and universally, to regarding the very idea of justice as essentially contestable (Alisdair MacIntyre 1973) emerging in a unique hybrid culture provoked by rigorous analytic confrontation between divergent traditions and contrary value systems. Since cultural diversity obtains within social hierarchies just as aggressively as it does across cultures, testimonies are required early in the process of treating global justice as an ongoing deliberative project, so that judicial interpreters come to know something about underclass experience and conditions prevailing in the expanding informal economic sector worldwide.